EXPLORING ISLAMIC FINTECH: A BIBLIOMETRIC APPROACH - Mohammad Irfan; Sylva Alif Rusmita (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
Introduction: In recent years, Islamic Fintech and bibliometric analysis in general have drawn more attention in the finance literature. In this study, all papers indexed in the Dimensions database that cover the wide topic of Fintech and Islamic Fintech from 2017 to 2023 are examined using bibliometric analytical tools.  Methods: The authors discovered 675 papers that met the set function, subject, and criteria requirements. The papers' publishing by knowledge area, annual study output, national contribution, author count, and most prestigious journals were all analysed. The co-occurrence of keywords and document citations was visually analysed using the VOS viewer. Filter the data set from "Islamic Fintech” or "Bibliometric Analysis” or "Literature Reviews”, and concluding the research on the 76 final publications. Results: According to the findings, the dimensions database includes depicts the second search on the keyword of "Islamic Fintech” or "Bibliometric Analysis”, than research found 97 publication from the different filed like, 51 publication form the articles, 19 publication from the edited book, 15 publication form the chapters, 7 publication form the preprint, 4 from proceedings, and 1 from the monograph. Research limitations/implications : The bibliometric analysis carried out was confined to Dimensions data. Other national and international databases were not taken into account for this research. Conclusion and suggestion: Between 2017 and 2023, this study examined relevant studies on bibliometric analysis of Islamic Fintech Publication. The study presents a concise review of the literature accessible to researchers working in this area and provides recommendations for future research.